SPACES as a Counseling Approach in Treating Traumatic Experiences of the Typhoon Sendong Victims in Iligan City, Philippines - Pamplona, Myla Pilar S. (JPAIR Multidisciplinary Research, 2016)
The creation of a counseling approach for Filipinos remains a big challenge to counselors. Foreign counseling methods do not meet the needs of Filipino clients in addressing diverse issues. Moreover, different regions have different perspectives as far as problems, etiology, manifestations and solutions are concerned. The study aimed to show that SPACES, an innovative counseling approach, can be a tool in counseling. SPACES is multidimensional counseling approach designed by Dr. Alexa P. Abrenica, a Filipino psychologist, which evaluates the spiritual life, physical health, attitude, creativity in solving problems, emotional health, satisfying work and support network of Filipino clients. It is believed that a difficulty in one dimension will affect and bleed into other components. The author used SPACES during a counseling service mission at Iligan City, Philippines after the onslaught of typhoon Sendong in 2012. In the case of Mina, a 43-year old widow and a victim of typhoon Sendong, SPACES was proven effective after its results were used to provide her treatment. SPACES allowed the client let go of all the negative thoughts from the traumatic experience and considered it as an enriching experience. The use of SPACES proves that counseling approaches must resonate culturally to achieve the real purpose of counseling.
Keywords: Psychology; counseling approach; SPACES; Iligan City; Philippines